LONG-PERIOD TRENDS IN GLOBAL SEISMIC AND GEOMAGNETIC ACTIVITY AND THEIR RELATION TO SOLAR ACTIVITY - Odintsov S.; Boyarchuk K.; Georgieva K.; Kirov B.; Atanasov D. (My University, 2006)
In the present paper, we are comparing the century-scale trends and decadal variations in seismic activity, and are looking for a relation to century-scale and decadal changes in solar and geomagnetic activity. The possible mechanisms of solar activity influences on seismic activity are also discussed. © 2006 Elsevier Ltd. All rights reserved.
Keywords: SEISMIC AND GEOMAGNETIC ACTIVITY; SOLAR